Prevalence and virulence of Vibrio species isolated from raw shrimp from retail markets in Reynosa, Mexico. (1st September 2020) - Guardiola‐Avila, I.; Martínez‐Vázquez, V.; Juárez‐Rendón, K.; Alvarez‐Ainza, M.; Paz‐González, A.; Rivera, G.
Abstract: In this study, the prevalence of Vibrio cholerae, Vibrio parahaemolyticus, Vibrio mimicus, Vibrio vulnificus and Vibrio spp. in shrimp from retail markets in Reynosa, Mexico was determined. A total of 765 isolates, identified as Vibrio spp. (59·1%), V. cholerae (17·8%), V. mimicus (6·7%) and V. parahaemolyticus (4·6%), were obtained; V. vulnificus was not detected. Most of the strains were isolated from supermarkets (48·1%), followed by street vendors (37·3%) and retail stores (14·6%). Moreover, several virulence genes were identified in V. cholerae : tox R (100%), Omp U (76·5%), hly A (76·5%), VPI (19·9%) and tcp A (5·1%); in V. mimicus : vmh (100%), wzb (74·5%), pil F (54·9%), VPI (43·1%), Omp U (29·4%) and tdh (9·8%); and in V. parahaemolyticus : tox R (100%), tlh (100%), VP1680 (51·4%) and VPI (11·4%). These results show the low safety of this food and the potential risk to consumers' health, since this product in Mexican cuisine is sometimes served raw or semi‐cooked. Significance and Impact of the Study: This study shows the prevalence of pathogenic Vibrio cholerae, Vibrio mimicus and Vibrio parahaemolyticus isolated from shrimp that is commercialized in Reynosa city. This could represent a risk to consumers' health, since outbreaks related to shrimp contaminated with Vibrio have been previously reported. Additionally, shrimp fishing has a major role in Mexico's economy.